Impact of equine sperm phospholipase C zeta content and sperm tail components on cleavage rates after intracytoplasmic sperm injections of equine and bovine oocytes - Amoroso G. Sanches, Fabio, author; Carnevale, Elaine, advisor; Black, Jerry, advisor; Hatzel, Jennifer, committee member; Graham, James K., committee member; Veeramachaneni, Rao, committee member (Colorado State University. Libraries, 2020)
Intracytoplasmic sperm injection (ICSI) is used in equine assisted reproductive medicine to generate offspring when other procedures fail. However, for some stallions, ICSI is not successful in producing embryos. This could be caused by multiple factors associated with stallion or mare gametes, which result in low cleavage and embryo development rates. Phospholipase C zeta (PLCz) has been identified as a sperm- associated factor that contributes to oocyte activation and is correlated to ICSI success in other species. We hypothesized that sperm population content of PLCz is associated with cleavage after ICSI and that components of the sperm tail, by virtue of containing oocyte activation factors can activate oocytes and induce cleavage. For the experiments, ICSI was performed using equine sperm with "High" or "Low" PLCz content on bovine oocytes (heterologous model) and equine oocytes to confirm results in the same species. More bovine oocytes (P=0.04) and equine oocytes (P=0.01) cleaved after injections with sperm having High PLCz content than Low PLCz content (bovine: High, 33/62, 53% and Low, 19/56, 34%; and equine: High, 9/10, 90% and Low 4/12, 33%). The addition of equine sperm tail components to the injection of sperm from a stallion with low PLCz population during ICSI improved (P<0.05) cleavage rates of bovine oocytes. In conclusion, PLCz content of equine sperm population was associated with cleavage rates following ICSI. Bovine oocytes provided a heterologous model to estimate the ICSI potential of an equine sperm population before use with equine oocytes, providing a more feasible and less costly system to evaluate sperm. Components of the equine sperm tail appear to assist activation for sperm from stallions with low PLCz content.
Keywords: equine; PLCz; theriogenology; ICSI; andrology; sperm